1985
DOI: 10.1148/radiology.156.3.4023229
|View full text |Cite
|
Sign up to set email alerts
|

Use of CT in the evaluation of cochlear otosclerosis.

Abstract: Otosclerosis (otospongiosis) occurs when the hard endochondral bone of the otic capsule is replaced by spongy vascular foci of haversian bone. Using computed tomography (CT), we studied the ears of 32 selected patients with mixed or sensorineural hearing loss (one patient had normal hearing); 24 were suspected of having otosclerosis. CT proved valuable in detecting cochlear otosclerosis, foci of demineralization, and changes in bony texture and enables the easy recognition of subtle radiographic findings. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 0 publications
0
37
0
5
Order By: Relevance
“…9,10 Otosclerotic foci have been extensively depicted with CT in these areas where cartilaginous remnants are commonly found, namely the fissula ante fenestram and the middle otic layer. 4,11 Therefore, it would be interesting to consider the hypoattenuated focus in the anterior otic capsule as a potential site of otosclerosis and to determine its role in the development of anterior pericochlear otosclerosis.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Otosclerotic foci have been extensively depicted with CT in these areas where cartilaginous remnants are commonly found, namely the fissula ante fenestram and the middle otic layer. 4,11 Therefore, it would be interesting to consider the hypoattenuated focus in the anterior otic capsule as a potential site of otosclerosis and to determine its role in the development of anterior pericochlear otosclerosis.…”
Section: 2mentioning
confidence: 99%
“…1,2 Pericochlear hypoattenuated foci in the middle layer of the otic capsule are routinely observed with thin-section CT in asymptomatic patients where they can mimic pathologic conditions. 3,4 It has been speculated that these foci correspond to cartilage remnants, fibrocartilage, nonmineralized bone, or bone marrow, but this still remains debated. Moreover, in pediatric patients, these hypoattenuated foci have been mostly depicted in the area of the fissula ante fenestram, 5,6 whereas less attention has been paid to other locations, such as the anterior otic capsule.…”
mentioning
confidence: 99%
“…Na doença retrofenestral, é possível evidenciar na TC uma imagem de luscência ou hipodensidade pericoclear (sinal do duplo halo), o que representa uma faixa de desmineralização endocondral da cóclea ocasionada pela confluência das lesões otoscleróticas ativas. O envolvimento dos canais semicirculares, meato acústico interno, vestíbulo e do endósteo da cóclea também podem ser identificados em pacientes com otosclerose retrofenestral [6][7][8][9][10][11][12] . O objetivo deste estudo é identificar, através da utilização da TCAR, os principais focos otoscleróticos retrofenestrais.…”
Section: Introductionunclassified
“…6 Mafee et al studied 32 cases of mixed and sensorineural hearing loss where HRCT proved valuable in detecting otosclerosis, foci of demineralization, and change in bony structure. 7 Present study includes 2 cases of mixed hearing loss in which HRCT shows radiolucent foci involving anterior margin of oval window and spreading to oval window ( Table 9). The present study included 3 cases of congenital ear disease present with (anotia, decreased hearing, deformed pinna, facial palsy) out of which 3 have auricular dysplasia 1 (33.33%) has ossicular fusion and 2 (66.66%) have aberrant course of facial nerve, these HRCT findings are in agreement with findings of Meyer et al 8 It was also found that the extent of auricular anomalies corresponds to the severity of change in the external auditory canal, excessive inclination of the external and internal auditory canals, dysplasia of the middle ear cavity and ossicles.…”
Section: Resultsmentioning
confidence: 99%